2021
DOI: 10.1002/npr2.12217
|View full text |Cite
|
Sign up to set email alerts
|

Elevated depressive symptoms among newer and younger healthcare workers in Japan during the COVID‐19 pandemic

Abstract: Aim Depression is a frequent outcome of long‐term stress, but no studies have examined depression rates among Japanese healthcare workers fighting the COVID‐19 pandemic. Therefore, we conducted a web‐based interview of hospital employees to assess depression prevalence and factors. Methods This observational cohort study was conducted from July to August, 2020, as part of a mandatory health checkup of Juntendo University Hospital employees (Tokyo, Japan). A total of 423… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…There is also a growing body of literature illuminating the complexity of new graduate nurse transition during the Covid-19 pandemic. Collectively the findings highlight experiences of fear, uncertainty and self-doubt (Aukerman et al, 2022;García-Martín et al, 2021;Kovanci & Atlı Özbaş, 2022) alongside negative impacts on psychological health (Katsuta et al, 2021;Nayor et al, 2021), while other findings reveal themes of resilience and commitment to the profession of nursing (Casey et al, 2021;Nayor et al, 2021;Sessions et al, 2021). Some of these emerging experiences have also been reflected in past endemics, however the longevity and magnitude of the Covid-19 pandemic may serve to mediate experiences in ways that may not parallel these past experiences.…”
Section: Background and Purposementioning
confidence: 92%
“…There is also a growing body of literature illuminating the complexity of new graduate nurse transition during the Covid-19 pandemic. Collectively the findings highlight experiences of fear, uncertainty and self-doubt (Aukerman et al, 2022;García-Martín et al, 2021;Kovanci & Atlı Özbaş, 2022) alongside negative impacts on psychological health (Katsuta et al, 2021;Nayor et al, 2021), while other findings reveal themes of resilience and commitment to the profession of nursing (Casey et al, 2021;Nayor et al, 2021;Sessions et al, 2021). Some of these emerging experiences have also been reflected in past endemics, however the longevity and magnitude of the Covid-19 pandemic may serve to mediate experiences in ways that may not parallel these past experiences.…”
Section: Background and Purposementioning
confidence: 92%
“…In a study, it was reported that between 20% and 30% of nurses tending to the COVID-19 patients were in a state of high mental distress, and the increase in the number of patients was a factor affecting their mental health problems and the intention to resign [ 6 ]. Another study in a university hospital showed that approximately 30% of young nurses with depression showed depressive symptoms during the pandemic [ 16 ]. Nurses in closer contact with patients are considered more likely to have mental health problems than other healthcare employees.…”
Section: Introductionmentioning
confidence: 99%
“…18 datasets conducted in 11 countries during COVID-19 reported the prevalence of probable mental health disorders across different timepoints (details in S10 Appendix) (Algattas et al, 2021; Baumann et al, 2021; Cai et al, 2020; Castioni et al, 2021; Chene et al, 2021; De Kock et al, 2022; Doulias et al, 2021; Gündoĝmuş et al, 2021; Katsuta et al, 2021; Lasalvia et al, 2021; Lasalvia et al, 2020; Li et al; Magnavita et al, 2021a, b; Magnavita et al, 2020; Moore et al, 2021; Mosolova et al, 2021; Noaimi et al, 2021; Schmid et al, 2021; Shechter et al, 2021; Th’ng et al, 2021). Due to the variation in timepoints, differences in context, and the small number of studies, the temporal relationship between prevalence rates of mental health outcomes and the COVID-19 pandemic were narratively synthesised to avoid combining quantitative data inappropriately.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies (Katsuta et al, 2021; Moore et al, 2021) compared pre-pandemic rates with COVID-19 rates in hospital HCWs. One study (Katsuta et al, 2021) (n-T1=2529, n-T2=2501) found no significant difference in the prevalence of depression pre-pandemic and during the COVID-19 pandemic among hospital HCWs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation